Correction: Duetting electronic structure modulation of Ru atoms in RuSe2@NC enables more moderate H* adsorption and water dissociation for hydrogen evolution reaction. Issue 18 (28th April 2022) - Chen, Ding; Lu, Ruihu; Yao, Youtao; Wu, Dulan; Zhao, Hongyu; Yu, Ruohan; Pu, Zonghua; Wang, Pengyan; Zhu, Jiawei; Yu, Jun; Ji, Pengxia; Kou, Zongkui; et al.
Abstract : Correction for 'Duetting electronic structure modulation of Ru atoms in RuSe2 @NC enables more moderate H* adsorption and water dissociation for hydrogen evolution reaction' by Ding Chen et al., J. Mater. Chem. A, 2022, 10, 7637–7644, ; https://doi.org/10.1039/d2ta01032a .